(untitled) (Economic studies journal, 2024)
The main objective of this study is to know the level of availability of intellectual capital in its various dimensions at the National Bank of Algeria in Biskra, To achieve the objectives of the study, we relied on the descriptive analytical method, A precise questionnaire was designed and prepared according to (Likert scale) as a main tool for collecting primary data and statistical information from the study sample, By application to the National Bank of Algeria in Biskra, A number of (50) questionnaires were distributed to the study sample, A number of (44) distributed forms were received, The study reached several results, the most important of which are: The study showed that the level of availability of intellectual capital in its various dimensions in the bank under study was high according to the study scale, Based on the results of the study, the researchers recommended a number of recommendations, the most prominent of which are: The bank under study must enhance the elements of intellectual capital and its various dimensions, And to encourage continuous competition among employees with creative abilities, And to provide sufficient material and moral incentives to those who innovate and create